REBELLION AND DIPLOMACY IN INTERNATIONAL POLITICS IN THE CONTEXT OF THE RWANDAN CRISIS (2012)
Rebellion and diplomacy have played considerable roles in international politics in the last two decades. Both phenomena, however, have failed to resolve many crises and conflict of interests that have plagued the African continent. Studies have been done on the causes and effects of these conflicts. However, substantial attention has not been paid to the centrality of diplomacy in the conflict processes. By drawing the contours of successes and failures of diplomacy, this study investigated the consequences, challenges and effects of diplomacy in the Rwandan conflict, one of the deadliest conflicts in Africa. The study utilized both primary and secondary data. Survey method, in-depth interviews and Focus Groups Discussions (FGDs) were utilized to source primary data. These include: 146 unstructured key informant interviews with 14 academic staff of the National University of Rwanda (NUR), two staffers of the International Criminal Tribunal for Rwanda (ICTR), four journalists, four members of the International Committee of the Red Cross (ICRC), seven members of the Association of Widows and Victims of Genocide amongst Women (AVEGA), 14 genocide site guides, nine Gacaca members and four war crime prisoners. Eleven FGDs involving undergraduate and postgraduate students of NUR were also conducted. Secondary data were drawn from library and archival documents. The study employed a descriptive and content analysis approach. Ethics of humanitarian intervention was a major factor that made decisive action slow, or impossible in emergency situations by the Organisation of African Unity (OAU). Similar provisions in the OAU charter principles made the organisation incapable of effectively dealing with ethno-chauvinistic conflicts. Focus Groups Discussions emphasized competing and incompatible goals and exercise of state power as sources of many conflicts in Africa. Rebel movements emerged where democratic processes failed, leading to civil wars and genocides. The growing number of these crises, conflicts and civil wars therefore, led to the increasing demand for new conflict resolutions, transformations, and post-conflict reconciliatory initiatives that require direct intervention beyond the purview of the O.A.U charter. Such interventions require defining, acceptable and workable power sharing arrangements. In the specific case of Rwanda, these requirements were complicated by neo-colonial manipulations, inciting ethnic hatred and genocide. Thus, the failures of African and international diplomacy were central to the occurrence of genocide and its devastating effects in Rwanda. These failures were repeated in the post-conflict reconstruction process, where political intrigues and diplomatic inconsistencies in the workings of ICTR prolonged the process of healing and reconciliation amongst the people. The Rwandan case revealed how rebellion could degenerate into genocide in a divided society, where leadership is overwhelmed by sectarian struggles. Effective diplomacy will require a larger regional framework of conflict management that affords the opportunity for quick intervention. African leaders within the framework of African Union (AU) should encourage their peers to respect the sanctity of human life, and its centrality to development and governance, by creating an effective mechanism for solving conflicts in Africa. The proposed AU standby force needs to be established and strengthened, to encourage diplomatic methods of negotiation and compromise in order to prevent a quick recourse to violence by opposition forces.